Desenvolvimento e Cooperação Internacional: um olhar sobre os projetos do Brasil e Estados Unidos na MINUSTAH - Correa, Paulo Gustavo (Meridiano 47 - Journal of Global Studies, 2017)
This paper submits to critique the Brazilian proposal to create a new paradigm for international cooperation from its role in MINUSTAH. We compare some aspects of Brazilian projects in Haiti with U.S. projects. We analyzed documents of the Brazilian Cooperation Agency (ABC) and United States Agency for International Development (USAID).